Structure and electronic properties of δ-Bi2O3 tuned by vacancy and doping: A first-principles study. Issue 1 (1st January 2021) - Huang, R.Z.; Wei, Y.Y.; Gao, T.F.; Li, C.M.; Jiang, C.H.
Abstract: Pure Bi2 O3 with high ionic conductivities is considered as a candidate material for an electrolyte in solid oxide fuel cells and oxygen separation membranes. However, its lower structural and thermal stability prevent it application in ion conductivity and photocatalysis at suitable temperatures. Metal oxides are usually used to stabilize its structure to lower temperatures and the underlying mechanism is still unclear. To shed light on the issue, vacancy ordered structures of pure and doped δ-Bi2 O3 have been studied by first-principles calculations. It have been shown that the structure with combined <110> and <111> vacancy arrangements is energetically favorable compared to either <100>, <110> or <111> vacancy ordered structures. Electronic structure analyses have further verified that δ-Bi2 O3 has a semiconductor character with an energy gap of 2.0 eV, consistent with the experiment results. The site occupation of doping ions is further analyzed by formation energy, geometry and electronic structures. It is evident that the substitution sites of doping ions depend on the type of the doping ions. The ions with large ion sizes tend to occupy the Bi(2) sites while the ions with small ion sizes tend to occupy the Bi(1) sites. At the same time, the probability of the Y ions occupying the oxygen vacancy sites and the optical properties of the Y-doped Bi2 O3 are explored. Our investigations reveal that the electronic structure of oxides could be tuned by vacancy and interstitial defects for better conductivity, photocatalytic properties.